DEFINING THE KEY-PARAMETERS OF INSURANCE PRODUCT IN ISLAMIC INSURANCE - G. Z. Vakhitov; Z. A. Enikeeva (Russian Journal of Economics and Law)
Objective: to define the range of actuarial calculations in Islamic insurance, to study the main differences of the traditional and Islamic insurance, to define, what changes in calculations entail the above differences. Methods: mathematical modeling, probabilistic analysis of insurance risks, adaptation of methods of actuarial mathematics to the principles of Islamic insurance. Results: the mathematical form of the takaful-fund models is presented, the distribution is analyzed of a random variable of the resulting insurance fund or the insurance company balance in a particular fixed insurance portfolio. Scientific novelty: calculation are presented of the optimal tariff rate in takaful. Islamic insurance is an innovative area of insurance industry. Actuarial calculations that meet the Sharia rules are still being developed. The authors set the new tasks of actuarial calculations, including the specified changes in the calculation of the optimal tariff rate imposed by the Islamic insurance principles. Practical value: the results obtained can be used in the actuarial calculations of the Islamic insurance companies.